Mainstreaming Interfaith Education: Countering Radicalism by The Innovation of Model Interfidei Schools - Arhanuddin Salim (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2022)
Â Abstract This paper evaluates interfaith education in Indonesia through a case study of Interfidei's school program in Yogyakarta. Interfaith education is one of Indonesia's most common ways of addressing interfaith tensions. This qualitative research uses a comparative descriptive method with data collection techniques using in-depth interview techniques, observation, and documentation. The research location is in Yogyakarta, observing the implementation of the Interfaith School at the Interfidei Foundation, Yogyakarta. Interfidei school is an excellent interfaith school in Indonesia. The form of interfaith education developed by Interfidei focuses on interfaith community activities and is booming with the interpersonal approach to reduce prejudice between participants. However, interreligious education focusing on interpersonal relations fails to bring about significant inter-religious understanding because it avoids discussing fundamental theological issues and differences. The results showed that theological and philosophical approaches are needed to bring about a profound change in interfaith knowledge in Indonesia rather than the current focus on interpersonal relations. Abstrak Tulisan ini mengevaluasi pendidikan lintas agama di Indonesia melalui studi kasus program sekolah Interfidei di Yogyakarta. Pendidikan lintas agama adalah salah satu cara paling umum di Indonesia untuk mengatasi ketegangan antar agama. Penelitian kualitatif ini menggunakan metode deskriptif komparatif dengan teknik pengumpulan data menggunakan teknik wawancara mendalam, observasi, dan dokumentasi. Penelitian dilakukan di Yogyakarta, pada Sekolah Lintas Agama di Yayasan Interfidei. Sekolah Interfidei adalah sekolah unggulan antar-agama di Indonesia. Bentuk pendidikan lintas agama yang dikembangkan oleh Interfidei menitikberatkan pada kegiatan komunitas lintas agama dengan pendekatan interpersonal untuk mengurangi prasangka antar peserta. Namun, pendidikan antar-agama yang menitikberatkan pada relasi interpersonal menghasilkan pemahaman antar-agama yang signifikan karena menghindari pembahasan persoalan dan perbedaan teologis yang mendasar. Hasil penelitian menunjukkan bahwa pendekatan teologis dan filosofis diperlukan untuk membawa perubahan mendalam dalam pengetahuan lintas agama di Indonesia daripada fokus hubungan interpersonal saat ini.